Массовые выступления на городских улицах как жанр политического карнавала: возможное толкование событий ноября–декабря 2004 года в Киеве - Тамаш, П. (Социология: теория, методы, маркетинг, 2007)
The author suggests analysis of the so-called "Orange Revolution" events through the different paradigmatical approaches as (a) the Postponed radical Perestrojka connected with reconfiguration of political roles for the classical intelligentsia, as (b) a post-modern revolt, (c) a late-modern human rights campaign, as (d) the democracy export,(e) street politics with mass mobilization, directed to replacement or dismissal of post-Soviet power elites. The conclusion about a hybrid reality of this event with the focus on emergence of the post-Soviet middle class, its civil structures and ideologies is argued.